PENINGKATAN HASIL BELAJAR MENGGUNAKAN MODEL NUMBERED HEAD TOGETHER PADA PEMBELAJARAN PKN DI KELAS V - Agustiana, Agustiana; Halidjah, Siti; Asran, Mastar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstrakGeneral purpose of research to improve student learning outcomes through Numbered Head Together model. Descriptive Method in the form of Classroom Action Research, is collaborative. Data collection techniques used are the technique of direct observation and measurement by means of data collection is the Student Worksheet. Setting research with the subject of Teachers / Researchers and students of class V amounted to 24 students. 1) The ability of teachers planning learning Numbered Head Together model experienced an average increase of 0,29 with an average value of 3.79. 2) The ability of teachers to implement learning model Numbered Head Together experienced an average increase of 0,29 with an average value of 3,64. 3) Students' learning outcomes of the Numbered Head Together model experienced an increase in cycles of 25 with an average score of 87,5. Conclusion: The results of action research conducted in the process of learning Civics Education can improve student learning outcomes. Suggestions: Teachers should better recognize the character of students so that teachers can more condition students to remain calm when learning is taking place.Â Keywords: Improved Learning Outcomes of Students, Model Numbered Head Together Citizenship Education.Â